PRODUKSI POLIHIDROKSIALKANOAT DART AIR LIMBAH INDUSTRI TAPIOKA : KONSISTENSI PRODUK, PENGARUH PH DAN PERBAIKAN PROSES PENGAMBILAN PHA - Setyawaty, Rety
ABSTRACT: POLYHYDROXYALKANOATES (PHA) PRODUCTION FROM TAPIOCA WASTEWATER : PRODUCT CONSISTENCY, pH INFLUENCE, AND PHA RECOVERY PROCESS REFINING By: Rety Setyawaty 23003005 Department of Chemical Engineering Institut Technology Bandung (ITB) Plastic has played an important role in human life nowadays. The using of plastic has been spreading widely from the household to industries needs. This is caused by the natural characteristic of plastic, which are flexible, light in weight, and durable. However, the waste of conventional plastic has been becoming a serious enviromental problem in many countries, especially in Indonesia. Polyhydroxyalkanoates (PHA) is one popular example of plastic, which can be used to substitute the conventional plastic. PHA can be degraded easily by microorganisms in a certain time so that it is very enviromentally friendly. However, the price of the substrate still gave large influence on the cost of production of PHA. Indeed, most process of PHA production are based on pure cultures, which often causes high cost of the selection of the microorganisms and the process itself. An interesting alternative to pure cultures utilized for PHA production until now is the use of mixed cultures such as the activated sludge from wastewater treatment plants. The influent wastewater contains readily biodegradable carbon sources that are often transformed into PHAs by microorganisms and store the PHAs in their cells before being used for their growth. Hence, activated sludge is presently considered a possible source of biodegradable plastics (Satoh et al., 1998). The use of mixed cultures, i.e. activated sludge, instead of pure cultures brings some advantages, e.g. the process can be simplified as it does not need sterile condition, and the cost of the substrate can be extremely decreased by using the wastewater itself as the carbon source. The microorganisms in activated sludge consume the carbon from wastewater to grow, causing COD reduction, and start to accumulate PHAs in their cells when the environment changes into a certain condition, i.e. low dissolved oxygen environment. To support that potential condition, the activated sludge system may be modified in a sequencing batch reactor (SBR), which can easily handle the feeding, aeration, and decanting period without changing the reactor. The purpose of this research are to see the consistency of the amount of PHA produced for every run which was done, to evaluate the effect of pH to the production performance, and to find out PHA recovery process refining. The melting point of PHA yield in this research was between 100 - 160Â°C with the content of hydroxyvalerat compound was between 3 - 42.8% without the pH controller. The melting point of PHA yield by using pH controller was between 100 - 110Â°C with the content of hydroxyvalerat compoud was between 35 - 42.8%. Without the pH controlling and the ratio of aerob-anaerob time of 2:4 (h/h), the maximum concentration of PHA produced was 0.292 g/g cell whereas the maximum concentration of PHA produced by using the pH controller and the same ratio of aerob-anaerob time was 0.212 g/g cell. Based on statistic analysis, the fourth run gave a consistent amount of PHA produced while the first, second, and the third run did not give a consistent amount of PHA produced. Refining in the recovery process gives a good performance of plastic.